2022
DOI: 10.15377/2409-9813.2021.08.2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Conditions for the Measurement of Soil Inorganic Nitrogen with a Micro-Plate Reader

Abstract: There are numerous methods for measuring inorganic nitrogen (N) in soils, but many of these are complex or require expensive equipment. In order to seek an accurate and rapid measurement method, we optimized the conditions for soil inorganic nitrogen (N) (NH4+-N and NO3–N) determination with a micro-plate reader; a systematic study was carried out. The effects of extraction regent concentrations, ratios of extraction solution to the soil, extraction time, extracted solution storage methods and time, and reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Compared with un-buffered KCl, extraction with DIW significantly underestimated the NH4 + concentration in the three soils and the NO3 -concentration in the fluvo-aquic soil (Figure 2d-f). Tu et al (2021) [30] also found that the measured concentrations of NH4 + and NO3 -in KCl extracts were 1.6-2.6 and 1.1-1.8 folds higher than those in DIW, respectively. Lim et al (2018) [16] showed that DIW-extracted NO3 -concentrations were only 50-60% of those extracted by 2 mol L -1 KCl.…”
Section: Soil Nh4 + and No3 -Concentrationsmentioning
confidence: 83%
See 3 more Smart Citations
“…Compared with un-buffered KCl, extraction with DIW significantly underestimated the NH4 + concentration in the three soils and the NO3 -concentration in the fluvo-aquic soil (Figure 2d-f). Tu et al (2021) [30] also found that the measured concentrations of NH4 + and NO3 -in KCl extracts were 1.6-2.6 and 1.1-1.8 folds higher than those in DIW, respectively. Lim et al (2018) [16] showed that DIW-extracted NO3 -concentrations were only 50-60% of those extracted by 2 mol L -1 KCl.…”
Section: Soil Nh4 + and No3 -Concentrationsmentioning
confidence: 83%
“…In recent years, a large number of studies have been conducted on the factors affecting the determination of soil NH 4 + and NO 3 − , including the extraction method [30], the concentration of the extractant [30], the storage method [31], the shaking time [30], etc. However, the effects of these factors on soil NO 2 − concentration have not been systematically reported.…”
Section: Nitrite (Nomentioning
confidence: 99%
See 2 more Smart Citations
“…The pH and EC of the soil and biochar were determined using soil/biochar slurry to water (1:5, w/v) suspensions. The content of AN and NN in the soil and biochar was determined by extracting with potassium chloride solution and using a colorimetric method (Tu et al, 2021). The TN content in the soil was determined using the Kjeldahl method (Lin et al, 2020).…”
Section: Pot Experimentsmentioning
confidence: 99%